2016
DOI: 10.3389/fnhum.2016.00532
|View full text |Cite
|
Sign up to set email alerts
|

Fluoxetine Does Not Enhance Visual Perceptual Learning and Triazolam Specifically Impairs Learning Transfer

Abstract: The selective serotonin reuptake inhibitor fluoxetine significantly enhances adult visual cortex plasticity within the rat. This effect is related to decreased gamma-aminobutyric acid (GABA) mediated inhibition and identifies fluoxetine as a potential agent for enhancing plasticity in the adult human brain. We tested the hypothesis that fluoxetine would enhance visual perceptual learning of a motion direction discrimination (MDD) task in humans. We also investigated (1) the effect of fluoxetine on visual and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…Furthermore, there are no prior reports of visual benefits from fluoxetine monotherapy in amblyopic patients, even though millions of patients, and presumably thousands of amblyopic patients, have used the medication over the past three decades. In addition, a recent placebo-controlled, double-blinded clinical study showed that 20 mg/day of fluoxetine for 19 days did not significantly affect visual perceptual learning in humans 40 . These prior studies support the theory that 20 mg/day of fluoxetine may not be a large enough dose to effectively modulate visual cortex plasticity in adult humans.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there are no prior reports of visual benefits from fluoxetine monotherapy in amblyopic patients, even though millions of patients, and presumably thousands of amblyopic patients, have used the medication over the past three decades. In addition, a recent placebo-controlled, double-blinded clinical study showed that 20 mg/day of fluoxetine for 19 days did not significantly affect visual perceptual learning in humans 40 . These prior studies support the theory that 20 mg/day of fluoxetine may not be a large enough dose to effectively modulate visual cortex plasticity in adult humans.…”
Section: Discussionmentioning
confidence: 99%
“…In adult animal models fluoxetine results in reduced GABAergic inhibition and increased BDNF expression, which results in reopening of the critical period (Maya-Vetencourt et al 2008, Bachatene et al 2013), but a study in humans did not find that fluoxetine enhanced perceptual learning (Lagas et al 2016). In humans the FDA-approved cholinesterase inhibitor donepezil seems to enhance perceptual learning, perhaps by shifting the excitation/inhibition balance towards the ‘immature’ state of greater excitation (Rokem et al 2010, Rokem and Silver 2013, Chamoun et al 2017).…”
Section: Reawakening the Critical Periodmentioning
confidence: 99%
“…In addition, a recent placebo-controlled, double-blinded, clinical study showed that 20 mg/day of fluoxetine for 19 days did not significantly affect visual perceptual learning in humans. 43 These prior studies support the theory that 20 mg/day of fluoxetine may not be a large enough dose to effectively modulate visual cortex plasticity in adult humans.…”
Section: Discussionmentioning
confidence: 60%